Učinek kakovosti družinskega okolja na otrokove prilagoditvene sposobnosti - Kreft, Ivana (Psihološka obzorja (Ljubljana), 2008)
The aim of the paper was to investigate how the quality of family environment is related to the child's adaptation capabilities. Child's adaptation was evaluated with a special assessment called SPP-3 (Systematic Psychological Assessment of a 3-year Old Child), that screens the population of 3-year olds to look for inadequate adaptation patterns. I assumed that in families where parents have higher education and where the environment is more stimulating children will show more effective and adaptive behaviour. Seventy-five children and parents who attended the psychological assessment in their regional hospitals first concluded the psychological examination (SPP-3) and then filled-in two questionnaires: The Family Environment Questionnaire (Zupančič, Podlesek, & Kavčič, 2004) and The Home Literacy Environment Questionnaire (Marjanovič Umek, Podlesek, & Fekonja, 2005). The results showed that quality of family environment does effect the child's adaptive capabilities and is associated with parental level of education. Of special importance for the child's socialization is the parentsć ability to use effective control (to have consistent and clear demands). Hypothesis that the level of parental education affects the child's adaptation capabilities was not confirmed. Perhaps the parents' relations with the child are of greater importance, and these are probably not related to parents' education. The results show that child's adaptation capabilities are associated with parenting methods, so preventive psychological counselling may also be used to help parents choose more effective methods in order to allow the child to develop effective adaptive behaviour.
Keywords: child; otroci; prilagoditvene sposobnosti; razvoj otroka; družinsko okolje; vzgoja; raziskave